Exercise barriers and the relationship to self-efficacy for exercise over 12 months of a lifestyle-change program for people with heart disease and/or diabetes. (1st April 2017) - Alharbi, Muaddi; Gallagher, Robyn; Neubeck, Lis; Bauman, Adrian; Prebill, Gabrielle; Kirkness, Ann; Randall, Sue
Abstract: Background: Barriers to exercise are common in people with coronary heart disease (CHD) and/or diabetes mellitus (DM), and may influence self-efficacy for exercise. Purpose: The purpose of this study was to describe the exercise barriers experienced by people who have CHD and/or DM participating in the Healthy Eating and Exercise Lifestyle Program and to determine whether these barriers influence self-efficacy. Methods: Participants ( n = 134) identified their barriers to exercise and completed the self-efficacy for exercise survey at baseline, at 4 months (following structured and supervised exercise) and at 12 months (following home-based exercise with three follow-up calls). Results: The sample mean age was 63.6 years (SD 8.5) and 58% were male. Barriers to exercise were reported by 88% at baseline, 76% at 4 months, and 47% at 12 months. The most common barriers were lack of motivation (40.3%), lack of time overall (30.6%), and lack of time due to family commitments (17.2%). Only motivation changed significantly over time from baseline (40%) to 4 months (23%, p = 0.040). Lower self-efficacy for exercise was associated with lack of motivation at 12 months only, more depressive symptoms at baseline and 4 months, and a CHD diagnosis and higher body mass index at 12 months. In contrast, male gender and having higher self-efficacy at baseline were associated with higher self-efficacy for exercise at 4 and 12 months. Conclusion: Patients identified many exercise barriers despite participating in a lifestyle-change program. Lack of motivation negatively influenced self-efficacy for exercise at 12 months. Other factors needing attention include baseline self-efficacy, depressive symptoms, being female, being more overweight, and having CHD.